2018
DOI: 10.1038/s41598-018-25699-9
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatic stellate cells secrete Ccl5 to induce hepatocyte steatosis

Abstract: Non-alcoholic fatty liver disease (NAFLD) encompasses a wide spectrum of disease severity, starting from pure steatosis, leading to fatty inflammation labeled as non-alcoholic steatohepatitis (NASH), and finally fibrosis leading to cirrhosis. Activated hepatic stellate cells (HSCs) are known to contribute to fibrosis, but less is known about their function during NAFLD’s early stages prior to fibrosis. We developed an ex vivo assay that cocultures primary HSCs from mouse models of liver disease with healthy he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…For example, Kim et al recently reported that CCR5 is expressed on hepatocytes and is involved in their ability to accumulate fat and promote steatosis and that CCL5 is secreted by hepatocytes during steatosis. [43][44][45] Our data suggest that there might be a direct effect of CCL24 on hepatocytes, although an indirect effect could not be completely ruled out. This effect, either direct or indirect, is novel and highly interesting and needs to be further elucidated in upcoming research on CCL24.…”
Section: Discussionmentioning
confidence: 62%
“…For example, Kim et al recently reported that CCR5 is expressed on hepatocytes and is involved in their ability to accumulate fat and promote steatosis and that CCL5 is secreted by hepatocytes during steatosis. [43][44][45] Our data suggest that there might be a direct effect of CCL24 on hepatocytes, although an indirect effect could not be completely ruled out. This effect, either direct or indirect, is novel and highly interesting and needs to be further elucidated in upcoming research on CCL24.…”
Section: Discussionmentioning
confidence: 62%
“…These findings were further confirmed in humans, showing increased circulating CCL20 protein levels in patients with NAFLD-related fibrosis (Chu et al 2018). Further data based on an elegant co-culturing system using primary liver cells pointed toward CCL5 as an important hepatic stellate cell-derived chemokine capable of mediating steatosis and pro-inflammatory responses in initially healthy hepatocytes (Kim et al 2018). Moreover, in vivo induction of CCL5 in response to high-fat diet was also shown to serve as an important regulator of vascular remodeling, revealing a role for CCL5 and its receptor in atherogenesis (Lin et al 2018).…”
Section: Hepatic Inflammation and Fibrosismentioning
confidence: 79%
“…Nonparenchymal hepatic cell types, including hepatic stellate cells (HSCs), contribute to coordinated fibrosis and progression towards NAFLD [67]. High levels of saturated FAs from the diet lead to the activation of HSCs, which, in turn, upregulate the production of proinflammatory cytokines (IL-34 and CCL5) [67,68]. Through lipid droplet breakage, HSCs remain a source of bioactive lipid species that may act extracellularly within the liver, enhance the lipotoxic effect of fat spillover and lead to a more severe spectrum of NAFLD [69].…”
Section: T2d Develops When Hepatic Autoregulation Is Lost-a Matter Ofmentioning
confidence: 99%